2015
DOI: 10.1002/chem.201502197
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Strong Boron–Fluorine and Silicon–Fluorine σ‐Bonds: Theoretical Understanding and Prediction

Abstract: The oxidative addition of BF3 to a platinum(0) bis(phosphine) complex [Pt(PMe3)2] (1) was investigated by density functional calculations. Both the cis and trans pathways for the oxidative addition of BF3 to 1 are endergonic (ΔG°=26.8 and 35.7 kcal mol(-1), respectively) and require large Gibbs activation energies (ΔG°(≠)=56.3 and 38.9 kcal mol(-1), respectively). A second borane plays crucial roles in accelerating the activation; the trans oxidative addition of BF3 to 1 in the presence of a second BF3 molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…According to spectroscopic data, the formation of the Lewis pair [(Cy 3 P) 2 Pt→BF 2 Ar F ] constitutes the initial reaction step. This observation was supported by theoretical studies on trans ‐[(Cy 3 P) 2 Pt(BF 2 )(FBF 3 )] and [(Cy 3 P) 2 Pt(BFAr F )][BAr Cl 4 ], which are predicted to be formed by [(Cy 3 P) 2 Pt→BF 3 ] and [(Cy 3 P) 2 Pt→BF 2 Ar F ], respectively …”
Section: Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…According to spectroscopic data, the formation of the Lewis pair [(Cy 3 P) 2 Pt→BF 2 Ar F ] constitutes the initial reaction step. This observation was supported by theoretical studies on trans ‐[(Cy 3 P) 2 Pt(BF 2 )(FBF 3 )] and [(Cy 3 P) 2 Pt(BFAr F )][BAr Cl 4 ], which are predicted to be formed by [(Cy 3 P) 2 Pt→BF 3 ] and [(Cy 3 P) 2 Pt→BF 2 Ar F ], respectively …”
Section: Methodsmentioning
confidence: 58%
“…Furthermore, there is a precedent for the abstraction of a fluoride anion from a [PF 4 ] − complex in the literature: The reaction of [(Et 3 P) 2 Ir(CO)Cl 2 (PF 4 )] with BF 3 to give [(Et 3 P) 2 Ir(CO)Cl 2 (PF 3 )][BF 4 ] . Mechanisms related to that suggested for the transformation of 4 a into 3 a in Scheme have been predicted for the reaction of [(Me 3 P) 2 Pt→BF 3 ] with BF 3 to give trans ‐[(Me 3 P) 2 Pt(BF 2 )(FBF 3 )], and the reaction of [(Me 3 P) 2 Pt→SiF 4 ] with SiF 4 to give trans ‐[(Me 3 P) 2 Pt(SiF 3 )(FSiF 4 )], on the basis of DFT calculations . In these studies, intramolecular reactions have also been found to be unlikely due to energetically high‐lying transition states.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bertrand et al described af ormal 1,2-addition of as table (phosphanyl)(silyl)carbene with dimesitylfluoroborane,t hus resulting in ab orylated phosphorus ylide. [9] Thed iphenylcarbene 1 is ap rototypical transient carbene [10] with at riplet ground state and has been subject to alarge number of mechanistic studies using time-resolved or low-temperature spectroscopy. [8] According to recent DFT calculations by Kameo and Sakaki, this reaction is endergonic and has al arge activation barrier if only one BF 3 molecule is involved.…”
mentioning
confidence: 99%
“…As econd molecule of BF 3 is necessary to reduce the activation barrier and to make the reaction thermodynamically feasible. [9] Thed iphenylcarbene 1 is ap rototypical transient carbene [10] with at riplet ground state and has been subject to alarge number of mechanistic studies using time-resolved or low-temperature spectroscopy. [11][12][13][14] Recently,w ef ound that the interaction of the triplet state of 1 (T-1)with either H 2 O [15] or CH 3 OH [16] results in as witching of the spin state of the carbene from triplet to singlet (S-1)u pon formation of the strongly hydrogen-bonded complexes S-1···H À OH and S-1···H À OCH 3 ,r espectively (Scheme 2).…”
mentioning
confidence: 99%